(untitled) (Harlow, England, 2005)
The new book is intENDed for advanced undergraduate and graduate economics students whose requirements go beyond the material usually taught in undergraduate mathematics courses for economists. It presents most of the mathematical tools that are required for advanced courses in economic theory - both micro and macro. This second volume has the same qualities that made the previous volume so successful. These include mathematical reliability, an appropriate balance between mathematics and economic examples, an engaging writing style, and as much mathematical rigour as possible while avoiding unnecessary complications. Like the earlier book, each major section includes worked examples, as well as problems that range in difficulty from quite easy to more challenging. Suggested solutions to odd-numbered problems are provided. Key Features middot; Systematic treatment of the calculus of variations, optimal control theory and dynamic programming. middot; Several early chapters review and extEND material in the previous book on elementary matrix algebra, multivariable calculus, and static optimization. middot; Later chapters present multiple integration, as well as ordinary differential and difference equations, including systems of such equations. middot; Other chapters include material on elementary topology in Euclidean space, correspondences, and fixed point theorems. A website is available which will include solutions to even-numbered problems (available to instructors), as well as extra problems and proofs of some of the more technical results.
Keywords: Economics, mathematical